2009
DOI: 10.1002/j.2050-0416.2009.tb00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Release of Metal Ions by Brewer's Yeast During Successive Fermentations

Abstract: J. Inst. Brew. 115(1), 78-83, 2009Magnesium, zinc and calcium are the elements that are involved in the regulation of metabolic activity of yeast and/or other processes such as flocculation and cell division. The requirements for specific ions may be subject to changes in successive fermentations performed by the same biomass. The aim of this work was to analyze the changes in calcium, magnesium and zinc concentration in malt broth (9°P) and in the yeast over four successive fermentations. For all ionic specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
4
4
1
Order By: Relevance
“…of our results it can be concluded that successive fermentations of barley wort influence only the temporary release of zinc during fermentation (i.e. the time and intensity of a peak value) and not the initial and overall uptake, the latter being in discordance with other reports (18,19), most likely because of the low zinc concentration in our wort.…”
Section: Zinccontrasting
confidence: 91%
See 2 more Smart Citations
“…of our results it can be concluded that successive fermentations of barley wort influence only the temporary release of zinc during fermentation (i.e. the time and intensity of a peak value) and not the initial and overall uptake, the latter being in discordance with other reports (18,19), most likely because of the low zinc concentration in our wort.…”
Section: Zinccontrasting
confidence: 91%
“…In all cases, this increase reached a peak value in the first half of the fermentation, whereas its relative value was higher in later fermentations. This marked release of zinc by yeast has been observed previously and it was causally related to a drop in pH during the fermentation process, as that drop decreases the apparent stability constant of the zinc metal ion binders . This occurrence was presumably more considerable the more times the yeast slurry was reused.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…In the latter case (zinc supplemented samples), the increase in the magnesium ion in the beer after fermentation was much higher, reaching 50% (from 120 to 175 mg/L in both the 0.4 and 2 mg/L Zn 2+ supplementation trials). Similar trends were observed in study Poreda et al [43], which proved that increased content of zinc ions in wort can block the uptake of magnesium ions by the yeast. The current results show that in the case of L. brevis strain the uptake and release of magnesium ions is not affected by the zinc ion content.…”
Section: Metal Ion Release By Lab and Yeastsupporting
confidence: 89%
“…However, the metal ions have a significant impact on important parameters, including the conversion rate of sugar into ethanol, the final yield in ethanol, the growing and multiplying yeast, the cell viability, the stressors, and the yeast flocculation behavior [39,40].…”
Section: Introductionmentioning
confidence: 99%